Consumption of sugar-sweetened beverages and fast foods deteriorates adolescents' mental health - Ra, Jin Suk (Frontiers in Nutrition, 2022)
Sugar-sweetened beverage (SSB) and fast-food consumption is significantly associated with adolescents’ poor mental health. Furthermore, sugar-sweetened beverage and fast-food consumption might form clustered diet patterns with significant positive associations in adolescent high school students. Thus, the combined consumption of SSBs and fast foods may have more negative effects on mental health with synergetic effects than the sum of their independent consumption. This study aimed to identify the effects of combining the consumption of sugar-sweetened beverages and fast foods on mental health, including stress, depressive symptoms, and suicidal ideation among Korean high school students. Secondary data from 24,006 high school students were analyzed from the 17th Korea Youth Risk Behavior Web-based Survey, 2021. For statistical analysis, complex sampling analysis using the SPSS Statistics 26.0 software was applied for descriptive statistics and logistic regression analysis. In Korean adolescents, combining more than medium consumption of sugar-sweetened beverages and fast foods was associated with more stress, depressive symptoms, and suicidal ideation than their independent consumption. In addition, combining high consumption of sugar-sweetened beverages and low to high consumption of fast foods might have dose-dependent negative effects on stress, depressive symptoms, and suicidal ideation in Korean adolescents. Based on the results of this study, healthcare providers in schools and communities might develop various interventions including school/community-based feeding programs and policies targeting the restriction of SSB and fast-food consumption to improve adolescents’ mental health.